Vernal keratoconjunctivitis in adults: a narrative review of prevalence, pathogenesis, and management - Di Zazzo, Antonio; Zhu, Angela Y.; Nischal, Ken; Fung, Simon S. M. (Frontiers in Ophthalmology, 2024)
Vernal keratoconjunctivitis (VKC) is a chronic, progressive, allergic ocular surface disorder that can lead to sight-threatening complications. VKC occurs primarily in children and generally resolves about the time of puberty; however, case series and retrospective analyses indicate that approximately 10% of patients with VKC are adults, and that a subset of adult cases develop after puberty. Consequently, two age-related variants of VKC have recently been described: early-onset VKC-which manifests during childhood and persists into adult life-and late-onset disease, which emerges de novo after puberty. Although the signs and symptoms of adult and childhood VKC are similar, adult VKC is a long-lasting disease characterized by severe inflammation and increased risk of conjunctival fibrosis, which may place adult patients at higher risk for sight-threatening complications and adverse impacts on daily life. This review discusses the epidemiology, signs, symptoms, immunopathogenesis of adult VKC variants, and highlights current gaps in research and management of patients with this condition.